2015
DOI: 10.4103/0974-2727.151681
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bone Mineral Density, T-Scores and Serum Zinc between Diabetic and Non Diabetic Postmenopausal Women with Osteoporosis

Abstract: Context:Postmenopausal osteoporosis is a public health problem. Diabetics are at increased risk of osteoporosis-related fractures. Zinc (Zn) has a role in collagen metabolism, and its levels are altered in diabetes.Aims:The aim was to compare bone mineral density (BMD), T-score and serum Zn between diabetic and nondiabetic postmenopausal women with osteoporosis to see if they influence increased fracture risk in diabetes.Settings and Design:It is a cross.sectional study conducted at Department of Biochemistry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
2
13
1
1
Order By: Relevance
“…The incidence of Type 1 diabetes (T1D) with chronic hyperglycemic state has been globally rising during the past decades (Starup‐Linde & Vestergaard, ). Besides the well‐known diabetic complications such as retinopathy, nephropathy, and neuropathy, T1D is characterized also by poor bone health such as osteoporosis, even though the effect of Type 2 diabetes mellitus on bone mineral density (BMD) is controversial (Adil et al, ; Siddapur, Patil, & Borde, ). There is no consensus about the treatment for bone disorder induced by hyperglycemia (Zhukouskaya et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of Type 1 diabetes (T1D) with chronic hyperglycemic state has been globally rising during the past decades (Starup‐Linde & Vestergaard, ). Besides the well‐known diabetic complications such as retinopathy, nephropathy, and neuropathy, T1D is characterized also by poor bone health such as osteoporosis, even though the effect of Type 2 diabetes mellitus on bone mineral density (BMD) is controversial (Adil et al, ; Siddapur, Patil, & Borde, ). There is no consensus about the treatment for bone disorder induced by hyperglycemia (Zhukouskaya et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the women with a diagnosis of T2D were in very good glucose control with the median FPG below 7 mmol/L (6.1, IQR 5.5, 6.8), and a lower odds ratio of having osteoporosis in the distal forearm. In contrast, other studies found that T2D associates with higher BMD and T-scores [4,5] and that bone material strength is paradoxically reduced in women with DM2 in association with inadequate long-term glucose control (average HbA1c over 10 years) [27]. Our study adds to the growing body of evidence that reinforces the importance of considering glycemic control in examining the relationships between T2D and bone health and offers new perspectives on the beneficial role of traditional food for Inuit.…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, poorly controlled T2D on the basis of a haemoglobin A1c (HbA1c) ≥ 7.5% associates with greater BMD of lumbar spine and hip and greater fracture risk relative to controls, but this is not observed when T2D is adequately controlled [4]. Similarly, lumbar spine BMD of postmenopausal women with T2D on average in poor control (fasting plasma glucose (FPG) of 9.1 mmol/L), is higher than controls, but still in the osteoporotic range (Tscore −2.84 ± 0.42) [5]. There is also evidence that T2D associates with greater loss of BMD at the femoral neck, which may predispose to fracture [6].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of type 1 diabetes (T1D) with chronic hyperglycaemic state has been globally rising during the past decades (Starup-Linde and Vestergaard 2015). Besides the well-evident diabetic complications such as neuropathy, nephropathy and retinopathy, T1D is also characterized by poor bone quality such as osteoporosis, even though the affection of type 2 diabetes mellitus on bone mineral density (BMD) is controversial (Adil et al 2015;Siddapur et al 2015). The increase in the prevalence of osteoporosis induced by T1D has prompted researchers to explore novel biological reagents for the management of diabetic osteoporosis.…”
Section: Introductionmentioning
confidence: 99%